1989
DOI: 10.1029/jb094ib02p01563
|View full text |Cite
|
Sign up to set email alerts
|

A detection of non‐Newtonian gravity

Abstract: An experiment was performed to test Newton's inverse square law of gravitation. The test compared accurately measured gravity values along a 600‐m tower with upward continued gravity estimates calculated from ground measurements using algorithms based on Newtonian potential theory. Gravity measurements with an internal consistency of better than 20 μGal (1 μGal = 10−8 m/s2) were made on the tower at intervals of about 90 m using a single LaCoste‐Romberg model G gravimeter. Field measurements of gravity (using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Correcting for that, only one non-Newtonian force (instead of two as previously reported by Eckhardt et al [1988a]; see also Romaides et al [1989]) is required to fit the observed data in the tower experiment [Eckhardt et al, 1988b]. Correcting for that, only one non-Newtonian force (instead of two as previously reported by Eckhardt et al [1988a]; see also Romaides et al [1989]) is required to fit the observed data in the tower experiment [Eckhardt et al, 1988b].…”
Section: D Bartlett and W Tew (The Hill In Northmentioning
confidence: 99%
“…Correcting for that, only one non-Newtonian force (instead of two as previously reported by Eckhardt et al [1988a]; see also Romaides et al [1989]) is required to fit the observed data in the tower experiment [Eckhardt et al, 1988b]. Correcting for that, only one non-Newtonian force (instead of two as previously reported by Eckhardt et al [1988a]; see also Romaides et al [1989]) is required to fit the observed data in the tower experiment [Eckhardt et al, 1988b].…”
Section: D Bartlett and W Tew (The Hill In Northmentioning
confidence: 99%
“…63, 1902 (1989), who saw no deviation from Newtonian attraction within the noise of their tower experiment. 12 The density of the regional residual topography varies less than 10% from the nominal value of 2.67 g/cm 3 …”
mentioning
confidence: 96%
“…This procedure resulted in a set of terrain-corrected Bouguer gravity anomalies 9 that were upward continued using least-squares collocation with a covariance function appropriate for Bouguer anomalies and using a direct numerical integration of the upward continuation integral referenced to a Fourier-Bessel expansion. 3 The final step in the upward continuation involved computing the effect of restoring the masses (positive and negative) that were removed, thus returning the geophysical setup of the experiment to reality.…”
mentioning
confidence: 99%
“…Several borehole experiments have been conducted byStacey and his collaborators in the past 10 years (Stacey et al, 1981; Holding and Tuck, 1984;Holding et al, 1986 Eckhardt et al (1988) and Romaides et al (1989) claimed to observe a breakdown of Newtonian gravity that indicated nn additional attractive force.…”
Section: Borehole Vs Tower Experimentsmentioning
confidence: 99%